Revisiting the stealth trading hypothesis: Does time-varying liquidity explain the size-effect? - Gökhan Cebiroglu; Nikolaus Hautsch; Christopher Walsh (Goethe University Frankfurt, Center for Financial Studies (CFS), 2019)
Large trades have a smaller price impact per share than medium-sized trades. So far, the literature has attributed this effect to the informational content of trades. In this paper, we show that this effect can arise from strategic order placement. We introduce the concept of a liquidity elasticity, measuring the responsiveness of liquidity demand with respect to changes in liquidity supply, as a major driver for a declining price impact per share. Empirical evidence based on Nasdaq stocks strongly supports theoretical predictions and shows that the aspect of liquidity coor- dination is an important complement to rationales based on asymmetric information.
urn:nbn:de:hebis:30:3-509904
Keywords: G02; G10; G23; 330; stealth trading; price impact; liquidity elasticity; limit order book